ҚОРАҚАЛПОҚ ОИЛАЛАРИДАГИ АЖРАЛИШЛАРНИНГ ИЖТИМОИЙ ПСИХОЛОГИК САБАБЛАРИНИ ЎРГАНИШНИНГ АҲАМИЯТИ - Ибрагимова, Р.Ж. (SCIENCE and SOCIETY, 2019)
The article discusses the relevance and importance of studying the causes of divorces in Karakalpak families.
Keywords: family; divorce; socially psychological reason; to study; actuality relevance; importance; people; ethno- psychological features